Intercultural communication and competence: practices at the education level - Govaris, Christos; Komi, Niki; Καλδή, Σταυρούλα (Παιδαγωγικός Λόγος, 2024)
The present article focuses on the main theoretical aspects of the intercultural communication and intercultural competence in order to propose appropriate practices to be promoted at the education level. Based on the theoretical framework of Auerneheimer about intercultural communication and the challenges than can create barriers to intercultural communication we argue about the prerequisite of intercultural competence in order to propose certain practices in different levels of education